The Difficulties in Implementing Scientific Approach Based on 2013 Curriculum: A Case Study on One English Teacher - Madina, Sarah; Kardena, Absharini (Universitas Lancang Kuning, 2021)
This case study investigated the difficulties faced by an English teacher in implementing the scientific approach at one selected school in the district of Agam in West Sumatera, Indonesia. This qualitative research used semi-structured interview questions and an observation checklist as the instruments, with an English teacher as the data source. This study showed that the selected secondary English teacher in MTsN 3 Agam encountered eight significant difficulties in dealing with the implementation of stages of the scientific approach based on the 2013 curriculum in classroom activities. The English teacher’s difficulties included: (1) to determine the object that will be observed; (2) to determine how the way data recorded; (3) encouraging the students to ask; (4) to make the various media as the information resources; (5) deciding the duration of students to do the experiment activity; (6) to divide the time for evaluation; (7) to organize the student to analyze; (8) encouraging the student to present their work in front of the class. This study serves as a reminder for the preparation suitable strategies needed in adapting not only to the general teaching process, but also to the possible changes in the curriculum.